2014
DOI: 10.1016/j.jtcvs.2013.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis on multidetector computed tomography and mortality in patients with radiation-associated cardiac disease undergoing cardiac surgery

Abstract: In patients with radiation-associated cardiac disease undergoing cardiothoracic surgery, worsening pulmonary fibrosis is associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…We previously demonstrated that prior XRT exposure was an independent risk factor for increased long‐term mortality in patients undergoing cardiac surgery, including isolated CABG as well as combined CABG and valvular surgery . We have also reported that certain features may be potential predictors of adverse outcomes in patients with radiation‐associated cardiac disease, including abnormally thickened aortomitral curtain, reduced left ventricular global longitudinal strain, and worse degree of pulmonary fibrosis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that prior XRT exposure was an independent risk factor for increased long‐term mortality in patients undergoing cardiac surgery, including isolated CABG as well as combined CABG and valvular surgery . We have also reported that certain features may be potential predictors of adverse outcomes in patients with radiation‐associated cardiac disease, including abnormally thickened aortomitral curtain, reduced left ventricular global longitudinal strain, and worse degree of pulmonary fibrosis …”
Section: Discussionmentioning
confidence: 99%
“…Although our data on cause of death after surgery in the radiation group are limited, it appears that cardiopulmonary disease was a common mechanism of death. This is likely because of the possibility that prior chest (especially mediastinal) XRT exposure introduces multiple technical problems at the time of surgery due to radiation‐induced fibrosis of surrounding tissues, adhesions, and the presence of multiple cardiac lesions . Radiation patients frequently develop pulmonary complications as a result of open heart surgery, not the least of which are recurrent pleural effusions and severe restrictive lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…7,[20][21][22] We have previously demonstrated that previous XRT exposure was an independent risk factor for increased long-term mortality in patients undergoing cardiac surgery, including isolated CABG and combined CABG and valvular surgery. 7 We found that long-term mortality in patients with radiation-associated CAD undergoing isolated CABG may approach 46%, 7 whereas in the current study, we found long-term mortality after PCI to be 38% overall, up to 55% in patients treated with BA or BMS and 22% in patients treated with DES.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, we demonstrated that RACD patients have a high proportion of pulmonary comorbidities (including pulmonary fibrosis), which prolongs recovery and independently contributes to increased mortality. 34 …”
Section: Discussionmentioning
confidence: 99%